Influence of hydrocolloids on rheological properties of gluten-free dough based on corn flour - Benazir, Saima; Majeed, Darkshan; Maswal, Masrat; Gani, Murtaza; Mir, Shabir Ahmad; Dar, B N (Journal of Postharvest Technology, 2019)
The production of high quality bread made from ingredients other than wheat flour represents a major technological challenge, due to the  absence of the viscoelastic gluten compound. To tackle this problem, hydrocolloids such as CMC (Carboxymethyl cellulose), Tragacanth and  quince seed mucilage were incorporated into gluten-free formulations. The rheological characteristics of gluten-free doughs and their effect on  the quality of bread were studied based on corn flour. CMC increased the viscoelasticity and temperature stability of the dough and also higher  concentrations of CMC proved more productive. Tragacanth improved only the elasticity of the dough sample and made it more stiff and rigid.  Effect of quince seed mucilage was complex without much improving the rheological properties of the dough. The results showed that  incorporation of hydrocolloids improved the sensory scores of gluten free breads.
Keywords: Corn; hydrocolloids; dough rheology; carboxymethyl cellulose